2015
DOI: 10.1158/1078-0432.ccr-15-0198
|View full text |Cite|
|
Sign up to set email alerts
|

Aspirin Suppresses the Growth and Metastasis of Osteosarcoma through the NF-κB Pathway

Abstract: Purpose: Aspirin has recently been reported to reduce both the incidence and the risk of metastasis in colon cancer. However, there is no evidence at the cellular levels or in the animal models for such an effect of aspirin on cancer metastasis.Experimental Design: MTT assay, colony formation assay, and apoptosis assay were employed to analyze the effects of aspirin on the osteosarcoma cell viability in vitro. The NF-kB activity was measured by the NF-kB p65 luciferase reporter. Western blotting was used to an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
87
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 46 publications
6
87
1
2
Order By: Relevance
“…NF-κB is constitutively activated in a variety of human malignancies including prostate cancer and it could regulate the expression of many growth genes and the cell biological behavior [15, 28]. Thus, the role of NF-κB was determined in the cell invasion after aspirin treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…NF-κB is constitutively activated in a variety of human malignancies including prostate cancer and it could regulate the expression of many growth genes and the cell biological behavior [15, 28]. Thus, the role of NF-κB was determined in the cell invasion after aspirin treatment.…”
Section: Resultsmentioning
confidence: 99%
“…These processes lead to the liberated NF-κB entering the nucleus and regulation of a variety of downstream target genes [14]. Recently, it has been demonstrated that blockade of the NF-κB activation suppresses the release of many mediators by the cells, eventually modulating the cell survival, invasion, proliferation and death [12, 15]. Therefore, modulation of NF-κB and the related gene expression is though to be important for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An apparent discrepancy is that the concentrations required to exert these effects in cancer cells were significantly higher than that required to inhibit the activity of COX-1 or COX-2, suggesting the implications of other potential targets (12,13). Indeed, cell-based studies have demonstrated that aspirin inhibits cell proliferation, induces cell-cycle arrest and apoptosis in multiple cancer cell lines irrespective of COX-2 expression level (14)(15)(16)(17)(18). Aspirin can also sensitize cancer cell to TRAIL-induced apoptosis through a COX-2-independent mechanism (19).…”
Section: Introductionmentioning
confidence: 99%
“…Aspirin has been shown to be a potential agent for cancer chemoprevention, especially in colorectal cancer [14, 15], by inducing cancer cell apoptosis and inhibiting cell proliferation [16, 17]. Recently, aspirin has attracted strong attention for its effect on metastasis inhibition [18-21] and chemotherapy sensitivity improvement [22, 23]. Moreover, aspirin inhibits cancer cells proliferation and induces cancer cell apoptosis by preventing NF-κB activation [24, 25], interfering with ERK pathway [26] and inhibiting Wnt/β-catenin pathway [27].…”
Section: Introductionmentioning
confidence: 99%